Lymphocyte Activation Gene 3 Single-Nucleotide Polymorphisms in Bone Marrow Failure Diseases - Yingying Sun; Qiuying Cao; Xiaoyu Zhao; Chunyan Liu; Zonghong Shao (Analytical Cellular Pathology)
Introduction. Lymphocyte activation gene 3 (LAG3) is an inhibitory checkpoint protein expressed on activated T effector, T regulatory, and natural killer cells. The main function of LAG3 is the regulation of immune homeostasis. Several studies have suggested its role in malignant and autoimmune diseases. The objective of this study was to explore the association between LAG3 single-nucleotide polymorphisms (SNPs) and bone marrow failure diseases. Methods. Sixty-two patients newly diagnosed with bone marrow failure diseases in the Hematology Department of Tianjin Medical University General Hospital between January 2019 and December 2020 and 16 healthy controls were enrolled in this study. SNPs in LAG3 were investigated by performing Sanger sequencing, and the association of the detected SNPs with bone marrow failure diseases was analyzed. Results. Eleven SNPs were identified. Among them, the frequency of LAG3 rs1941928301 (C>T) was statistically different among the groups (P=0.013). It was higher in the myelodysplastic syndrome (MDS) group than that in the severe aplastic anemia (SAA) group (P=0.004) and that in the healthy control group (P=0.009). Conclusions. LAG3 rs1941928301 (C>T) might be associated with a higher risk of MDS. The detected LAG3 SNPs have no apparent effect on susceptibility to SAA and immune-related pancytopenia (IRP).